Integrasi Prinsip Ekonomi Syariah dalam Pertanian Berkelanjutan: Analisis Kasus Penggarapan 10 Hektar Lahan oleh Mahasiswa STIES Riyadlul Jannah Mojokerto di Desa Sumber Sumur, Krembung, Sidoarjo - Indrawati, Peni (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2022)
This research investigates the practice of Sharia-based agriculture conducted by 15 students from STIES Riyadlul Jannah Mojokerto, who were accompanied by Gus Abdulloh as a field supervising lecturer. The focus of the research is the cultivation of 10 hectares of land in Sumber Sumur Village, Krembung District, Sidoarjo Regency. With two harvests per year, each producing 27 tons, this study explores the impact of this practice on aspects of Sharia Economics. The cultivation process is carried out every morning from Monday to Thursday. The aim of this research is to identify the contribution of agricultural practices to fair income distribution, environmental sustainability, and the implementation of Sharia Economic principles. A qualitative research method was used to evaluate the participation of students and supervising lecturers in applying Sharia economic values in agricultural practices. The results of the study indicate that this agricultural practice successfully achieved high productivity while upholding the values of Sharia Economics. Fair income distribution among team members, attention to environmental sustainability, and the application of Sharia principles in economic transactions are key characteristics of this land cultivation.